E-Cigarettes and Gingival Pigmentation: A Public Health Concern Among Adolescents - Ermi Girsang; Firdha Muharraran; Irfan Aulia (Archives of The Medicine and Case Reports, 2025)
Electronic cigarette (e-cigarette) use has rapidly increased among adolescents, raising concerns about its impact on oral health. This study investigated the association between e-cigarette and gingival pigmentation among adolescents in a community setting. A cross-sectional study was conducted in November 2024 among members of the Vapers City of Medan community. Data were collected through a Google Form questionnaire and photographic documentation of participants' gingiva. The questionnaire assessed e-cigarette use patterns, including frequency and duration, and any concurrent use of conventional cigarettes. Gingival pigmentation was assessed through photographs, noting the presence and extent of pigmentation. Data were analyzed using SPSS, employing Chi-Square, correlation, and multivariable tests to determine the association between e-cigarettes and gingival pigmentation. E-cigarette use was significantly associated with gingival pigmentation (p=0.026). Adolescents who used e-cigarettes had a higher prevalence of gingival pigmentation compared to those who did not. Correlation analysis revealed a moderate positive correlation between e-cigarette use and gingival pigmentation severity (r=0.54, p=0.01). Duration and frequency of e-cigarette use were also weakly positively correlated with gingival pigmentation severity. Multivariable analysis confirmed that e-cigarette use (OR=4.5, 95% CI=1.2-16.8, p=0.024), duration of use (OR=2.1, 95% CI=1.1-4.0, p=0.028), and frequency of use (OR=1.8, 95% CI=1.0-3.2, p=0.046) were independently associated with gingival pigmentation. In conclusion, e-cigarette use is significantly associated with gingival pigmentation in adolescents. This finding underscores the potential adverse effects of e-cigarettes on oral health, highlighting a growing public health concern.